Improving critical thinking skills through discovery learning models assisted animation video on digestive system material - Yenny Anwar; Adeng Slamet; Ulfa Daniaty (JPBI (Jurnal Pendidikan Biologi Indonesia), 2023)
This research is quantitative research to determine the effect of using the Discovery Learning model to assist animation video on the critical thinking skills of students grade XI on the digestive system. The research method used is Quasi Experiment with a Non-equivalent Control Group Design and used purposive sampling. The research instruments used were multiple choice (pretest and post-test). Observation sheets, and students' questionnaire responses. Data on critical thinking skills outcomes were analysed using an independent sample t-test in the SPSS version 26.0 program. The result showed that the use of Discovery Learning models assisted animation video increased student critical thinking skills with a gain value of 41.43 and n gain of 0.64 in the medium category. The result of the hypothesis test shows the value of Sig. (2-tailed) 0.000 < 0.05 which means H0 is rejected and Ha is accepted. This shows that the Discovery Learning models to assist animation videos have a significant effect on student critical thinking skills of class XI of SHS 1 Lahat in the human digestive system. The implementation of learning has an excellent category, while student responses have an excellent and good category.